Pengelolaan Motivasi Belajar Siswa Di SMKN 1 Sudimoro Pacitan - PURNOMO, Kukuh; , Prof. Dr. Bambang Sumardjoko; , Dra. Wafroturrohmah, SE, MM (2015)
The purpose of this study was to describe (1) Management of learning motivation in learning in SMK 1 Sudimoro Pacitan. (2) Management of the implementation of learning motivation prakerin at SMK 1 Sudimoro Pacitan. This type of research is qualitative by design ethnography. The main subject of the study were teachers, principals and students. Data analysis used Analysis Interactive . Analysis Interactive was performed with data collection, data reduction, data display and conclusion drawing or verification. Test the validity of the data using triangulation. Research results indicate that (1) Planning the learning process includes learning objectives, teaching materials, teaching methods , learning resources, and assessment of learning outcomes. The learning process is a series of the most important in the formation and management of learning. Management of student motivation preferred to motivate students to learn and potential exploration. The things include: the provision of infrastructure, giving advice to students, the selection of relevant material, media selection, the selection of teaching methods (2) Implementation prakerin activity begins with a preliminary form of motivation and purpose prakerin. Earlier prakerin activities, teachers also expressed prakerin goals to be achieved and participation of teachers in improving student motivation in the form of a picture prakerin implementation prakerin consideration the working world, giving explanations of things that must be achieved during prakerin; Learning was developed to increase students' motivation. Management of student motivation is done in order to realize effective learning and satisfying. Improved learning is the essence of the educational institution. Of the increase of learning , school with a conducive environment to bring up the quality / quality of education is satisfactory. Thus it can increase student motivation in learning and prakerin.